Food, Texts, and Cultures in Latin America and Spain - Gómez-Bravo, Ana M. (Ana María); Climent-Espino, Rafael, 1977- (Book collections on Project MUSE., 2020)
"Approaches Hispanic and Latin American food from the perspective of literary and cultural studies. Fourteen essays apply a food lens to colonial studies, ethnic and racial studies, gender and sexuality studies, and studies of power dynamics, nationalisms and nation building, theories of embodiment, and identity"--